2018
DOI: 10.1038/s41598-018-34530-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of pre- and post-vitamin C treatments on UVB-irradiation-induced skin damage

Abstract: Several studies have reported the effects of vitamin C (L-ascorbic acid, AA) on ultraviolet B (UVB)-induced cell damage using cultured keratinocytes. However, the epidermis consists of multiple cell layers, and the effect of AA on UVB-induced damage to the human epidermis remains unclear. Therefore, we investigated the effect of AA on UVB-induced skin damage using reconstituted human epidermis. The reconstituted human epidermal surface was treated with 100 and 500 mM AA and cultured for 3 h before (pre-AA trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 52 publications
1
50
0
2
Order By: Relevance
“…Several studies have reported that ascorbic acid decreases UVB-induced ROS production, and prevents ROS-medicated DNA damage and apoptosis in epidermal keratinocytes [ 48 , 49 ]. Pre- and post-treatment of reconstituted human epidermis with ascorbic acid reduced UVB-induced cell death, apoptosis, DNA damage, ROS production, and the inflammatory response by suppressing tumor necrosis factor-α (TNF-α) production [ 50 ].…”
Section: Antioxidants and Interfollicular Epidermal Stem Cellsmentioning
confidence: 99%
“…Several studies have reported that ascorbic acid decreases UVB-induced ROS production, and prevents ROS-medicated DNA damage and apoptosis in epidermal keratinocytes [ 48 , 49 ]. Pre- and post-treatment of reconstituted human epidermis with ascorbic acid reduced UVB-induced cell death, apoptosis, DNA damage, ROS production, and the inflammatory response by suppressing tumor necrosis factor-α (TNF-α) production [ 50 ].…”
Section: Antioxidants and Interfollicular Epidermal Stem Cellsmentioning
confidence: 99%
“…Vitamin C could reduce oxidative stress production and inflammation to achieve protective effects. Researches showed that vitamin C could suppress UVB-induced cell death, apoptosis, ROS production, and the inflammatory response by downregulating tumor necrosis factor-α (TNF-α) expression [14,15]. Moreover, UVB irradiation of vitamin-deficient animals resulted in severe corneal injury and -inflammatory response [16].…”
Section: Introductionmentioning
confidence: 99%
“…In human skin in vivo and pig skin, the topical application of aqueous solution containing 15% vitamin C and stabilized with 1% vitamin E and 0.5% ferulic acid at low pH (as observed in formulation 1 and 2) reduces UVA radiation–induced erythema 20,22 . In addition, the administration of vitamin C in the medium protects reconstituted human epidermis or keratinocyte 3D cultures against DNA damage, inflammation, and apoptosis induced by UVA and UVB radiation 17,43 . However, some participants have reported redness and burning on their face after application of the anti‐aging moistures with 30% vitamin C 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In the dermis, vitamin C promotes the synthesis of elastic and collagen fibers in humans and rodents 10‐14 . In addition, topical administration of vitamin C protects skin against UV radiation–induced oxidative damage in pig models or reconstituted human epidermis 15‐17 . Nonetheless, the stability of such vitamin C formulations is essential for maximizing the protective effect.…”
Section: Introductionmentioning
confidence: 99%